Mood Regulatory Actions of Active and Sham Nucleus Accumbens Deep Brain Stimulation in Antidepressant Resistant Rats - Kale, Rajas P.; Nguyen, Thanh Thanh L.; Price, J. Blair; Yates, Nathanael J.; Walder, Ken; Berk, Michael; Sillitoe, Roy V.; Kouzani, Abbas Z.; Tye, Susannah J. (Frontiers in Human Neuroscience, 2021)
The antidepressant actions of deep brain stimulation (DBS) are associated with progressive neuroadaptations within the mood network, modulated in part, by neurotrophic mechanisms. We investigated the antidepressant-like effects of chronic nucleus accumbens (NAc) DBS and its association with change in glycogen synthase kinase 3 (GSK3) and mammalian target of rapamycin (mTOR) expression in the dorsal (dHIP) and ventral (vHIP) hippocampus of antidepressant resistant rats. Antidepressant-resistance was induced via daily injection of adrenocorticotropic-hormone (ACTH; 100 µg/day; 15 days). Portable microdevices provided continuous bilateral NAc DBS (130Hz, 200µA, 90µs) for 7 days. A control sham electrode group was included, together with ACTH- and saline-treated control groups. Home cage monitoring, open field, sucrose preference and forced swim behavioral tests were performed. Post-mortem levels of GSK3 and mTOR, total and phosphorylated, were determined in the dHIP and vHIP using western blot. Robust reductions in forced swim test immobility were observed for DBS animals, relative to ACTH and saline groups. DBS and sham groups displayed elevated home cage psychomotor activity compared to ACTH and saline groups. No differences in locomotor activity were however observed in the open field test. Additionally, ACTH-treatment increased sucrose consumption, an effect that in turn was attenuated by DBS. We further observed increased levels of vHIP phospho-GSK3β and phospho-mTOR in DBS group compared to ACTH-treated animals. No differences in these protein levels were observed in the dHIP region. These data suggest that continuous NAc DBS has robust antidepressant-like effects in the ACTH-model of antidepressant resistance and that DBS upregulates phospho-GSK3β and phospho-mTOR in the vHIP region of the mood network.